The Use Of Media In ELT - Novasyari, Ressy (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2022)
Learning English is lifelong process and it needs the perfect strategies or techniques to keep learning it the whole life. Teaching and learning is a process that needs communication in delivering the material. This communication needs some tools to bridge the information from the source to the receiver. Technology keeps growing fast and it has become one of the needs that people should use in their daily life. Technology also brings its influences to the activities in the classroom during teaching and learning process. Teaching and learning process is complex and it needs some serious actions to make it success. The use of media itself help teachers in delivering the media, like textbook, whiteboard, or even teachers themselves act as the media in transferring the information. But unfortunately, it doesn’t really success to attract the students’ attention in learning English. Therefore, teaching and learning process is described as a fix and complex system which needs media to create an optimal result. Keywords : The Position, The Function and The advantages of Media